Comparative Study on the Effectiveness of Acapella Versus Conventional Physiotherapy in Enhancing Lung Volume in Patients with Recent Chest Infections - Bhakhtiani, Lakshay; Joshi, Nalin; Khilnani, G.C.; Gaurav, Kumar; Bera, Soumyabrata (Journal of Neonatal Surgery, 2025)
Background: Chest infections often compromise lung volume and pulmonary function due to mucus retention and reduced ventilation. While conventional physiotherapy (CPT) remains standard for respiratory recovery, Acapella — a positive expiratory pressure (PEP) device — offers a potentially effective, patient-friendly alternative. Objective: To compare the efficacy of Acapella versus conventional physiotherapy in improving lung volumes in patients recovering from recent chest infections. Methods: A prospective, comparative study was conducted involving two groups of patients post-chest infection. Group A received CPT (postural drainage, percussion, breathing exercises), while Group B used the Acapella device two sessions per day for three days at the same frequency. Lung functions- Forced Vital Capacity (FVC) and Forced expiratory Volume in one second (FEV1) were recorded pre treatment on Day 1 and post treatment on Day 3. Secondary outcomes included oxygen saturation, sputum clearance, and patient compliance. Results: Both groups demonstrated significant improvement in FVC and FEV1. Group A (Acapella) showed slightly greater gains in FEV1 and reported higher comfort and compliance. Conclusion: Acapella therapy is comparable to conventional physiotherapy in enhancing lung volume post-infection, with added benefits of patient comfort and ease of use. These findings support its integration into respiratory care plans, particularly in outpatient or home settings.